Custos de transação para a inovação: elementos relevantes da interação entre universidade e empresa - Graef, Nelinho Davi (2021)
This study aimed to analyze the relevance of transaction cost elements and their influence on the interaction between university and business, through technology transfer contracts, to generate innovation in Brazil. It is justified by its originality in applying the Transaction Cost Theory to the university-business interaction, explaining the interaction between the parties to generate innovation, through technology transfer contracts. In addition, the results generate subsidies for strategies, mechanisms and actions in companies and universities, as well as public policies to improve the interaction effectiveness. The research has a qualitative and quantitative approach. Firstly, eight interviews were carried out with professionals from these organizations and the data collected were useful to the quantitative research questionnaire elaboration and, above all, to complement the results analysis. The quantitative research consisted on applying a questionnaire to 155 respondents, obtaining 153 valid responses, from five regions of Brazil. The data collect were treated statistically, using exploratory analysis, principal components analysis and weights determination for factors and variables. The results show that in Brazil, the degree of interaction between university and companies through technology transfer contracts is of medium intensity. The interaction for innovation presents high transactional complexity, with high transaction costs. The main components analysis identified eleven relevant factors that explain the transaction between the parties, namely: Uncertainty, Negotiation Costs and Contract Management, Trust, Bureaucracy, Secondary Specific Assets and Intellectual Property, based on Transaction Cost Theory. In addition to these, are relevant factors, the Culture for Interaction, Innovation Systems, Institutional Environment, Profile and Relationship and Resources based on the Knowledge Economy and Institutional Environment.